ISO 9001 European Scoreboard: an instrument to measure macroquality - Sampaio, Paulo (2014)
Purpose: ISO 9001 certification is nowadays considered to be one of the most effective tools that can be adopted for guiding the management of Quality Systems. The stunning growth observed by these standards all over the world confirms a strong polarisation of enterprises’ interest in this practice. Owing to the wide incidence of this phenomenon, a deep investigation of ISO 9001 diffusion over time is mandatory and of importance. In line with our previous publications, this paper derives from a research project that we are conducting in Portugal in order to develop the ‘ISO 9001 European Scoreboard’, aimed at studying and ranking European Union (EU) countries based on the diffusion of quality management systems. Methodology/approach: In order to achieve such a goal, the authors have performed a set of statistical analyses over public data sets. Findings: Based on the model developed and the analyses performed, we were able to identify clusters of countries with different ISO 9001 evolution stages, derived from the ISO 9001 per 1000 inhabitants’ scores and countries’ growth indexes. Originality: With this scoreboard, we are able to categorise and rank countries based on the quality management systems evolution (growth rates) over the past few years. Ultimately, such an ‘ISO 9001 European Scoreboard’ will be an instrument to provide a comparative assessment of quality management practices over the EU states, leading to the dynamic evaluation of their ‘macroquality’ levels achieved, according to such a standard. We believe that such results provide an additional important contribution to the study of management systems diffusion/evolution, aimed at providing more fact-based insights and understandings.